Indonesia’s defense acquisition strategy - Matthews, Ron; Maharani, Curie; Jupriyanto; Wu, Shang Su (Taylor & Francis, 2025)
Indonesia is a huge archipelagic state, whose maritime security faces a growing strategic challenge from China. Jakarta's ability to respond, however, is hampered by its low share of military expenditure in national income. The resultant unaffordability means that military capability is dependent on loans from overseas’ contractors and banks to fund weapons acquisition. Consequently, Indonesia’s acquisition strategy has been focused on closing the gap between capability aspirations and budgetary reality. It represents a case study of unorthodox funding options, comprising export credits, countertrade and institutional loans. In turn, Indonesia’s acquisition pathways have been shaped by budgetary inadequacy, and include 2nd hand equipment markets, barter and international technology-sharing programs. Future acquisition policy reform is essential to remove the inefficiencies associated with the present cost-minimization approach.
Keywords: 44 Human Society; 4408 Political science